Multidimensional impact of severe mental illness on family members: systematic review - Wubalem Fekadu; Awoke Mihiretu; Tom K J Craig; Abebaw Fekadu (BMJ Open)
Objective The impact of severe mental illnesses (SMIs) is not limited to the person with the illness but extends to their family members and the community where the patient comes from. In this review, we systematically analyse the available evidence of impacts of SMI on family members, including parents, grandparents, siblings, spouses and children.Data sources PubMed, PsycINFO, Embase and Global Index Medicus were searched from the inception of each database up to 9 November 2019. We also did manual searches of grey literature.Eligibility criteria We included studies that assessed the impacts of SMI on any family member. We excluded studies in admitted clinics and acute wards to rule out the acute effect of hospitalisation.Data extraction Two reviewers extracted data independently using the Cochrane handbook guideline for systematic reviews and agreed on the final inclusion of identified studies.Risk of bias The quality of the included studies was assessed using effective public health practice project quality assessment tool for quantitative studies.The review protocol was registered in the PROSPERO database.Results We screened a total of 12 107 duplicate free articles and included 39 articles in the review. The multidimensional impact of SMI included physical health problems (sleeplessness, headache and extreme tiredness.), psychological difficulties (depression and other psychological problems) and socioeconomic drift (less likely to marry and higher divorce rate and greater food insecurity). Impacts on children included higher mortality, poor school performance and nutritional problems. However, the quality of one in five studies was considered weak.Conclusions Our review indicated a high level of multidimensional impact across multiple generations. The serious nature of the impact calls for interventions to address the multidimensional and multigenerational impact of SMI, particularly in low/middle-income countries. Given the relatively high number of studies rated methodologically weak, more robust studies are indicated.PROSPERO registration number CRD42018064123.